Olfactory responses of Conotrachelus psidii (Coleoptera: Curculionidae) to hosts and conspecific odors - SILVA-FILHO, GILSON; BAILEZ, OMAR; VIANA-BAILEZ, ANA M. (Revista Colombiana de Entomología, 2012)
Conotrachelus psidii (Coleoptera: Curculionidae) is one of the most important pests of guava plants, Psidium guajava (Myrtaceae). Guava plant is the natural host of this weevil suggesting that volatile compounds from odor of different parts of the plant may be attractive to this insect. The main goal of this research was to determine if host or conspecific odors can act as attractants to guava weevil. The olfactory responses of the guava weevil were tested with a Y-tube olfactometer. The odors included green and ripened fruits, leaves and flower buds of P. guajava, guava weevils and their feces. Stimuli were tested singly and in combinations. Flower buds odors were attractive to C. psidii males suggesting the presence of host kairomones. Males and females weevil feces attracted both male and female weevils, indicating the existence of aggregation pheromones or allelochemicals (undigested plant compounds) in the feces. Further studies should be made to conclude from the nature of these substances. Identification and synthesis of the semiochemicals that attract the guava weevil would allow developing new strategies for monitoring and controlling this pest.